Efficacy and safety of etanercept biosimilar rhTNFR-Fc in Chinese patients with juvenile idiopathic arthritis: An open-label multicenter observational study - Xu, Xuefeng; Liu, Xiaohui; Zheng, Wenjie; Xiao, Jihong; Li, Xiaozhong; Wu, Ling; Zou, Lixia; Ouyang, Qian; Shangguan, Yaoyao; Lin, Kezhao; Dai, Xiaomei; Chen, Yuanling; et al. (Frontiers in Pediatrics, 2022)
Background: Etanercept biosimilar recombinant human TNF-α receptor II: IgG Fc fusion protein (rhTNFR-Fc) has showed its efficacy and safety in Chinese patients with rheumatoid arthritis. However, data on rhTNFR-Fc’s application in juvenile idiopathic arthritis (JIA) is limited. Methods: A prospective, observational, multicenter study was performed at 6 institutes in China from July 2020 to December 2021. In a 24-week follow-up, patients with JIA including polyarticular JIA and enthesitis related arthritis received rhTNFR-Fc plus methotrexate (MTX) treatment. The primary outcome parameters were improvements of cJADAS-10 (clinical Juvenile Arthritis Disease Activity Score), and the secondary outcome parameter was an inactive disease. Results: 60 patients completed at least 12-week follow-up, and 57 completed 24-week follow-up. They had high C reactive protein values (11.6 mg/L) and cJADAS-10 (14.6) at baseline. Thirteen patients had morning stiffness. 33 patients showed synovial thickening, and 34 showed bone marrow edemas on MRI. Ultrasonography demonstrated significant joint effusions in 43 patients. The cJADAS-10 sharply decreased from 14.66 at the baseline to 2.4 at 24 weeks of rhTNFR-Fc therapy, respectively (P < 0.01). About half of patients achieved inactive disease at 24 weeks of therapy. Compared with the baseline, the number of patients with morning stiffness, joint effusions, bone marrow edema and synovial thickening on MRI significantly decreased at 24 weeks. Adverse events were consistent with known side effects of biologic agents. Conclusions: The present study indicated that the combination of rhTNFR-Fc and MTX significantly improve symptoms and disease activity of children with JIA. This study suggests etanercept biosimilar rhTNFR-Fc as an effective and safe therapy for children with JIA.